2018
DOI: 10.22201/igeof.00167169p.2018.57.4.2107
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de asperezas de sismos recientes en la zona de subducción de Michoacán-Colima-Jalisco, México

Abstract: Se determinaron de manera sistemática los modelos de deslizamiento de los sismos de magnitud Mw mayor a 7 ocurridos desde el año 1980 en la zona de subducción de Michoacán-Colima-Jalisco utilizando ondas P y SH registradas a distancias telesísmicas y una parametrización que permite una amplia flexibilidad en la duración de la dislocación sobre el plano de falla. Para los distintos eventos las áreas de valores altos de deslizamiento no se empalman y forman un patrón entrelazado de asperezas adyacentes con espac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Also, in general, it is observed that the events that have a magnitude of Mw 6.9 to 7.1 have a rise time of about 3s. This is consistent with what Martínez-López and Mendoza (2018) have observed. This information would be useful for quick, real-time slip model determination studies.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Also, in general, it is observed that the events that have a magnitude of Mw 6.9 to 7.1 have a rise time of about 3s. This is consistent with what Martínez-López and Mendoza (2018) have observed. This information would be useful for quick, real-time slip model determination studies.…”
Section: Discussionsupporting
confidence: 93%
“…The stress drop determined for this event is less than 10bars. This value is consistent with the stress drop observed for interplate events in seismogenic coupling zones (Allmann and Shearer, 2009;Martínez-López and Mendoza, 2018). The drop stress determined for the 2021 Acapulco event is consistent with the values obtained for the 1982 doublet occurred in Ometepec, Guerrero (Astiz and Kanamori, 1984).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations